Clinical characterization of patients with schizophrenia and 16p13.11 duplication: A case series - Hiroki Kimura; Itaru Kushima; Masahiro Banno; Toshiya Inada; Akira Yoshimi; Branko Aleksic; Norio Ozaki (Wiley, 2023)
Abstract Background Chromosome 16p13.11 duplication is a well‐known genetic risk factor for schizophrenia (SCZ) (odds ratio = 1.84). However, no case reports focusing on patients with SCZ and 16p13.11 duplication have been published. Therefore, here, we report the detailed clinical cases of four patients with SCZ and 16p13.11 duplication who were identified in our previous whole‐genome copy number variant (CNV) study. Case Presentation In the four patients with SCZ and 16p13.11 duplication detected by array comparative genomic hybridization, one patient was found to have treatment‐resistant SCZ and an additional pathogenic rare CNV. Two of the four patients in this study had environmental risk factors that may have been involved in the development of SCZ. Conclusions The results of this case series suggest that a genetic cohort study would be useful for evaluating which genetic and environmental risk factors could better explain the variable expressivity of 16p13.11 duplication. Furthermore, this work could be useful for elucidating the pathophysiology of SCZ.